Anti-LGBTQ Hate Crimes in Miami-Dade County, Florida, 2005-2019 - Kutateladze, Besiki ([Verlag nicht ermittelbar], 2022)
The goal of this study is to enhance public safety and community well-being through effective identification, investigation, and prosecution of anti-LGBTQ hate crimes in Miami. The investigators examined victimization experiences, victim and offender characteristics, crime reporting outcomes, victimization consequences, case processing, as well as the criminal justice system's challenges and opportunities for reform. The project focuses on the hate crime victimization within Miami's Latine community.